The The Influence of Perceived Ease, Islamic Lifestyle, and Religiosity on the Consumptive Behavior Buy Now Pay Later Users of Generation Z in Jepara - Reynaldo Faisal Ardiansyah; Mahmudatus Sa'diyah (LP2M IAIN Palopo, 2026)
The development of financial technology (fintech), specifically buy now pay later (BNPL) services, has driven changes in the consumption patterns of generation Z, making them increasingly vulnerable to consumptive behavior. From an Islamic economic perspective, this phenomenon is a crucial issue as excessive consumption contradicts the principle of wasatiyah and the prohibition of israf and tabdzir. This study aims to analyze the influence of perceived ease of use, Islamic lifestyle, and religiosity on the consumptive behavior of generation Z BNPL users in Jepara Regency. This study employs a quantitative approach with an associative research type. The sampling technique used was purposive sampling on 100 active BNPL users. Data were analyzed using multiple linear regression with SPSS 26 software. The results showed that simultaneously, perceived ease of use, Islamic lifestyle, and religiosity significantly influenced consumptive behavior with a contribution of 8.6%. Partially, perceived ease of use had no significant effect on consumptive behavior, Islamic lifestyle had a positive and significant effect, while religiosity had a negative and significant effect. These findings indicate that a symbolic Islamic lifestyle potentially drives consumption (halal lifestyle), while religiosity functions as an effective inner control in suppressing consumptive behavior. This study provides important implications for strengthening Islamic financial literacy that emphasizes the internalization of substantive religious values, rather than merely halal lifestyle symbols, in facing the massive growth of digital financial services.